NARASI RADIKALISME DAN KETAKUTAN | RADICALISM NARRATION AND FEAR - Justin L Wejak (Institut Filsafat dan Teknologi Kreatif Ledalero, 2018)
Abstract: Indonesian history has been filled with many radical ideas and movements aiming to bring about radical changes in the direction of the nation state. Yet radicalism has created fear and angst amongst communities. This paper examines the narrative of radicalism and fear as constructed in an Indonesian Catholic document published in 1967. The document narrates the historical and political events from Indonesia’s independence to the early years of Suharto’s New Order regime, with a particular focus on the Madiun incident of 1948 and the Crocodile Hole tragedy of 1965. The paper argues that the document scrutinized is nothing but a fear text, and the fear narrative as constructed in the text is related to radicalism – namely the leftist radicalism represented by the Indonesian communists pre-1965, and the rightist radicalism represented by religious (Muslim) radicals post-1965. This main argument is explained with reference to Martin Heidegger’s philosophy of fear, and it concludes that the fear experiences concerning the communist past is paralelled with the experiences of fear in recent times in relation to religious (Islamic) radicalism. Keywords: radicalism, fear, communists, Muslims, Catholics, Heidegger Abstrak: Sejarah Indonesia dililiti banyak ide dan gerakan radikal yang bertujuan untuk membawa perubahan radikal ke arah negara bangsa. Namun radikalisme telah menciptakan ketakutan dan kecemasan di antara masyarakat. Makalah ini mengkaji narasi radikalisme dan ketakutan yang dibangun dalam dokumen Katolik Indonesia yang diterbitkan pada tahun 1967. Dokumen tersebut menceritakan peristiwa sejarah dan politik dari kemerdekaan Indonesia hingga tahun-tahun awal rezim Orde Baru Suharto, dengan fokus khusus pada insiden Madiun dari 1948 dan tragedi Lubang Buaya 1965. Makalah ini berpendapat bahwa dokumen yang diteliti tidak lain adalah teks ketakutan, dan narasi rasa takut yang terkonstruksi dalam teks ini terkait dengan radikalisme - yaitu radikalisme kiri yang diwakili oleh komunis Indonesia pra-1965, dan radikalisme kanan yang diwakili oleh radikal agama (Muslim) pasca-1965. Argumen utama ini dijelaskan dengan mengacu pada filosofi rasa takut Martin Heidegger, dan disimpulkan pengalaman-pengalaman ketakutan mengenai masa lalu komunis dilumpuhkan dengan pengalaman-pengalaman ketakutan belakangan ini dalam kaitannya dengan radikalisme agama (Islam). Kata-kata Kunci: radikalisme, ketakutan, komunis, Muslim, Katolik, Heidegger